Cadmium-exposed population in Mae sot district, Tak province: 4 bone mineral density in persons with high cadmium exposure - Limpatanachote P. (2014)
Objective: To measure bone mineral density in cadmium-exposed persons aged 40 years and older that lived in the 12 contaminated villages in northwestern Thailand. Material and Method: Five hundred seventy three persons with urinary cadmium levels ≥ 5 μg/g creatinine during the 2004-2006 surveys were screened in 2007 for urinary excretion of cadmium, bone formation and resorption markers, and renal function markers. Calcaneus bone density was measured in each person by a dual-energy X-ray absorptiometry bone scanner. Results: The mean age of the study persons was 57 years old. The geometric mean level of urinary cadmium for women was significantly higher than that for men. Women had a lower mean of calcaneus bone density than men. The rate of osteoporosis in women (21.5%) was significantly higher than that for men (14.7%). Calcaneus bone density was negatively correlated with urinary excretion of calcium (in both genders) and crosslinked N-telopeptide of type I collagen (in women), after adjusting for other co-variables. Increasing urinary cadmium levels appeared to correlate with reduced bone density in women, but not in men. In both genders, urinary excretion of β2-microglobulin and N-acetyl-β-D-glucosaminidase was higher in persons with osteoporosis than those without. Conclusion: Bone mineral loss is correlated with urinary cadmium levels and renal dysfunction in this female population.